Blanca Nieves: A Philippine Version of Snow White - Marte, Alfredo Nathaniel L. (Review of Women's Studies; Vol 26 No 1-2 (2016): Review of Women's Studies Volume XXVI, Numbers 1-2 (January-December 2016), 2023)
A Philippine version of the popular western tale, Snow White exists in the form of a corrido in Hiligaynon titled Vida ni Principe Alfredo cag ni Blanca Nieves sa Guinharian sang Babiera (1912) by an author known as "Nipon." The direct source for "Blanca Nieves" is unknown, and while it resembles the Grimms' version closely, many details have been added to the basic tale. This paper shows how these details allow for a reading of Blanca Nieves that highlights an aspect of the tale that centers, not on the mother-daughter relationship, but on the "beauty myth" as the primary motivation for the story.